Fatty acid, tocopherol and carotenoid content of botanically diverse pastures rotationally grazed by ruminant livestock in Ireland - Michelle Kearns; Peter G. Dunne; Jean-Christophe Jacquier; Sabine M. Harrison; Raquel Cama-Moncunill; Gaspard Beaucarne; Helen Sheridan; Tommy M. Boland; Frank J. Monahan (Journal of Agriculture and Food Research, 2025)
Pasture samples from (i) perennial ryegrass (Lolium perenne, L.; (PRG), (ii) PRG + white clover (Trifolium repens, L. (WC); PRG + WC) and (iii) multi-species (MS; PRG, timothy (Phleum pratense L.), WC, red clover (Trifolium pratense L.), chicory (Cichorium intybus L.) and plantain (Plantago lanceolata L.) pastures were collected from rotationally grazed paddocks throughout 2021. Higher levels of the fatty acids (FA) C16:0, C18:2n-6c and C18:3n-3c occurred in late-season for all pastures. C18:2n-6c contents were higher in MS pasture compared to PRG and PRG + WC pastures for all seasons, whereas C18:3n-3c contents were higher in PRG pasture than PRG + WC and MS pasture in mid- and late-seasons. Higher levels of tocopherols and carotenoids were observed in late-season for all pastures. Although α-tocopherol concentrations were similar between pastures, γ-tocopherol and lutein concentrations were higher in MS pasture. In conclusion, MS pastures can produce equivalent FA concentrations, along with increased γ-tocopherol and lutein concentrations compared to PRG pastures.